Does the effect of employment protection depend on the composition of unemployment? - Andreas Bastgen (Journal for Labour Market Research, 2024)
I develop an equilibrium-matching model with job rationing and endogenous layoffs in order to investigate whether the composition of unemployment (rationing versus frictional) influences the way firing costs affect employment. The model suggests that firing costs lead to a strong adverse employment effect if unemployment is mainly caused by job rationing, whereas in labor markets driven by search frictions firing costs have only a negligible impact on employment. The paper tests this hypothesis using data on the adoption of wrongful-dismissal laws adopted by U.S. state courts during the 1970s and 1980s. Results indicate that for two of the three wrongful-dismissal laws investigated, unemployment composition is crucial for the induced employment effects.
Keywords: O31; J64; J65; O38; 330; Difference-in-difference; Employment protection; Firing costs; Rationing unemployment; Search unemployment; Search-and-matching; Wrongful-dismissal-laws